Safety, Tolerability, and Pharmacokinetics of Intravenous Doses of PF‐07304814, a Phosphate Prodrug Protease Inhibitor for the Treatment of SARS‐CoV‐2, in Healthy Adult Participants. Issue 12 (26th October 2022) - Zhu, Tong; Pawlak, Sylvester; Toussi, Sima S.; Hackman, Frances; Thompson, Kimberly; Song, Wei; Salageanu, Joanne; Winter, Erica; Shi, Haihong; Winton, Jennifer; Binks, Michael
Abstract: Studies on targeted antivirals for treatment of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), the cause of the ongoing pandemic, are limited. PF‐07304814 (lufotrelvir) is the phosphate prodrug of PF‐00835231, a protease inhibitor targeting the 3C‐like protease of SARS‐CoV‐2. This phase 1 study evaluated the safety, tolerability, and pharmacokinetics (PK) of single ascending intravenous doses of lufotrelvir (continuous 24‐hour infusion of 50, 150, 500, or 700 mg) versus placebo in healthy volunteers (2 interleaving cohorts: 1, n = 8; 2, n = 7). Each dosing period was separated by a washout interval (≥5 days). Treatment‐emergent adverse events, PK, and biomarker concentrations were estimated from plasma/urine samples. Lufotrelvir was administered to 15 volunteers (mean [SD] age 39.7 [11.8] years). No serious adverse events, discontinuations, or deaths were reported. Mean maximum observed concentration of PF‐00835231 (active moiety; 97.0 ng/mL to 1288 ng/mL) were observed between median time to maximum concentration of 14 to 16 hours after the start of the lufotrelvir infusion. Near‐maximum plasma concentrations of PF‐00835231 were observed ≈6 hours after infusion start and sustained until infusion end. PF‐00835231 plasma concentrations declined rapidly after infusion end (mean terminal half‐life: 500 mg, 2.0 hours; 700 mg, 1.7 hours). Approximately 9%–11% of the dose was recovered in urine as PF‐00835231 across doses. A continuous, single‐dose, 24‐hour infusion of lufotrelvir (50–700 mg) was rapidly converted to PF‐00835231 (active moiety), with dose‐proportional PK exposures and no significant safety concerns. A daily, 24‐hour continuous infusion of 270 to 350 mg is expected to maintain PF‐00835231 concentration at steady state/above effective antiviral concentrations. Further studies exploring lufotrelvir efficacy in patients with coronavirus disease 2019 are ongoing.